(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article highlights the linguistic and cultural features of lexemes expressing a person’s character. The paper presents a series of lexemes describing a person’s character, their categories, that is, positive and negative character traits of people, in particular women